3D Ensemble Simulation of Seawater Temperature – An Application for Aquaculture Operations - Shettigar, Nithin Achutha; Bhattacharya, Biswa; Mészáros, Lörinc; Spinosa, Anna; El Serafy, Ghada (Frontiers in Marine Science, 2020)
During the past decades, the aquaculture industry has developed rapidly, due to drop in wild fish catch. Water quality variables play a major role in aquaculture operations specifically, seawater temperature has a major impact on the metabolism of the fish species and therefore on the growth rate too. Since the fish farming business relies on the growth rate of the species to plan and operate the farm, seawater temperature becomes crucial information. With the availability of hydrodynamic modelling tools and global ocean information source such as Copernicus Marine Environment Monitoring Service, seawater temperature can be simulated for practically any coasts with a dynamic downscaling approach. But the simulated data needs to be assessed for uncertainties for enabling informed decision making using such model predictions. In this paper, a coastal 3D hydrodynamic model aiming at simulating seawater temperature is developed for the southern Aegean Sea, Greece using the Delft3D Flexible Mesh modelling tool. Seawater temperature is impacted by atmospheric forces; therefore, uncertainties are assessed for seawater temperature using ensemble atmospheric forcing functions of the European Centre for Medium-Range Weather Forecasts (ECMWF) ERA5. Spatial analysis of the uncertainty indicates regions of different seawater temperature behavior within the model domain. The seasonal behavior of the vertical temperature gradient suggests that farms need to adapt different operational strategies in different seasons to make the best use of the seawater temperature. The application of Copernicus Marine Environment Monitoring Service data along with ECMWF ERA5 ensemble atmospheric forcing members proves to be beneficial in analyzing the uncertainties both in spatial and vertical gradient of seawater temperature.